2009
DOI: 10.1111/j.1600-6143.2008.02481.x
|View full text |Cite|
|
Sign up to set email alerts
|

Long-Term Insulin-Independence After Allogeneic Islet Transplantation for Type 1 Diabetes: Over the 10-Year Mark

Abstract: Results of islet of Langerhans transplantation have markedly improved in recent years, but most patients still lose insulin independence in the long-term.We report herein the longest (over 11 years) case of insulin independence after allogeneic islet transplantation. The subject had a 27-year history of type 1 diabetes and received a single islet-after-kidney graft of 8800 islet equivalents (IEQ)/kg, pooled from 2 donors. Insulin was discontinued by 3 months posttransplant and the patient has remained off insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 18 publications
0
51
0
Order By: Relevance
“…1) [47••]. Notably, Davalli et al [48] and Berney et al [49] described two cases of long-term (>4 years and >11 years, respectively) successful intrahepatic islet transplantation into T1D patients chronically immunosuppressed for a prior kidney graft.…”
Section: Discussionmentioning
confidence: 97%
“…1) [47••]. Notably, Davalli et al [48] and Berney et al [49] described two cases of long-term (>4 years and >11 years, respectively) successful intrahepatic islet transplantation into T1D patients chronically immunosuppressed for a prior kidney graft.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the achievement of longer-term insulin independence is highly sought. Although independence out to 10 yr is possible (Berney et al 2009) this is certainly not standard. The focus of this work is to review the advances in islet transplantation that have made the current results possible and to look ahead at some of the future advances aimed at achieving these goals.…”
mentioning
confidence: 99%
“…Interestingly, it was reported that one exceptional T1D patient who remained insulin-free 11 years after islet transplantation had a significantly higher frequency of circulating nTregs, as compared to healthy age matched controls [71]. Similarly, IL-10 production by total PBMC isolated from islet transplanted patients who were insulin-independent was significantly higher, as compared to that produced by transplanted and insulin-dependent subjects [62].…”
Section: Tregs In Autoimmune T1d Patients Transplanted With Allogeneimentioning
confidence: 95%